The teaching of English as a lingua franca: a reflection - Salles, Michele Ribeiro; Gimenez, Telma (BELT - Brazilian English Language Teaching Journal, 2010)
When it comes to English language teaching, it becomes indispensable to discuss the implications of conceiving it as a lingua franca, specially when it is about a linguistic educational policy with more equality. Our purpose in this article is to forge thinking about the current status of the English language within the changes of the new patterns of communication that claim for redefinitions of objectives to its teaching. In order to do so, we present researcher’s opinions on the field, aiming to contribute to a critical thinking about the role of Teachers and Teachers Educators of this language.